New marketing strategy threatening the traditional healthcare businesses / Sarah Sabir Ahmad, Azfahanee Zakaria and Isma Fazlini Ismail - Sabir Ahmad, Sarah; Zakaria, Azfahanee; Ismail, Isma Fazlini (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2022)
Many new marketing strategies have evolved in the recent years due to the movements from traditional purchase behavior to online of customers. At first, customers were forced to adapt to online purchase, but as they get used to it, it became very handy and now online business becomes preferable business over the traditional. As COVID-19 attacked the world, the healthcare business became among the few industries which attracted many new entrants that became competitors to the existing ones. These new entrants came along with their new marketing strategies which overtook the traditional marketing methods. It soon became a threat to the existing businesses. This article discusses the methods the new entrants did to become successful in a short period and the solutions the existing businesses should adapt to if they want to remain significant and preferred in the industry.